Pemodelan EGARCH Return Saham, Emas, dan Cryptocurrency - Firdausia, Farah Amira; Nasrudin, Nasrudin (Politeknik Statistika STIS, 2023)
Financial investment is an investment made by economic actors in financial markets through various financial instruments such as stocks, gold, and cryptocurrencies. This study has the goal of modeling the volatility of stock returns, gold, and cryptocurrencies during the Covid-19 pandemic. The data used is secondary data with the daily highest price during the peak period of the Covid-19 pandemic with the period 1 November 2020 to 30 April 2022. Modeling volatility on stock returns, gold, and cryptocurrencies which are asymmetrical uses EGARCH(1,1), EGARCH(0,1), and EGARCH(1,1). The three investment instruments have a leverage effect, namely bad news has a greater impact than good news, and the estimated volatility gives the result that cryptocurrency is the riskiest instrument followed by gold than stock.